Peran Guru Agama Hindu Dalam Menanamkan Nilai Satya dan Ahimsa Pada Siswa di Sekolah Dasar Gugus VI Kecamatan Buleleng - Ketut Mangku; Ni Luh Gede Hadriani; I Nyoman Raka (Jayapangus Press, 2025)
The cultivation of character values based on Hindu teachings has a high urgency in addressing the phenomenon of moral crisis among the younger generation, including students. This study aims to analyze the role of Hindu religion teachers in instilling the values of satya (honesty) and ahimsa (non-violence) in elementary school students at Cluster VI, Buleleng District. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed interactively through data reduction, data presentation, and conclusion drawing. The findings show that: (1) satya and ahimsa are understood as ethical foundations within the Tri Kaya Parisudha teachings, which are relevant in shaping students’ noble character and empathy; (2) the role of Hindu religion teachers includes being role models and motivators, facilitators and mentors, as well as innovators who integrate these values into various school activities; (3) the implications observed are the improvement of honesty, discipline, and social awareness, along with the decrease of deviant behaviors such as bullying and disorderliness among students. This study affirms the importance of Hindu religion teachers as facilitators of values and agents of character formation. The success of instilling satya and ahimsa requires systemic, collaborative, and contextual support among schools, families, and communities.